2020
DOI: 10.1111/wej.12571
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Aspidisca cicada on nitrifying bacteria and the morphology of flocs in activated sludge

Abstract: Crawling ciliates play important role in activated sludge as they improve flocculation and remove loosely attached bacteria from the flocs. However, there are discrepancies concerning their influence on nitrifying bacteria and nitrification efficiency. We conducted a five weeks experiment in six bioreactors simulating the Sequencing Batch Reactor (SBR) process using activated sludge from a plant in start-up phase. Half of bioreactors were inoculated with dense Aspidisca cicada culture and the remaining bioreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…abundance (R S = 0.64, p < 0.05), and sulfite-reducing bacteria removal and number of taxa (R S = 0.79, p < 0.01). Sobczyk et al (2020) recently reported a correlation between the highest abundance of A. cicada and lowest total nitrogen in effluent, corroborating our results. Negative correlation was determined between effluent parameters and certain taxa: effluent conductivity and Opercularia coarctata abundance (R S = −0.62, p < 0.05), total bacteria in effluent and number of taxa (R S = −0.68, p < 0.05), total N in effluent and Vorticella sp.…”
Section: Municipal and Industrial Wastewatersupporting
confidence: 93%
“…abundance (R S = 0.64, p < 0.05), and sulfite-reducing bacteria removal and number of taxa (R S = 0.79, p < 0.01). Sobczyk et al (2020) recently reported a correlation between the highest abundance of A. cicada and lowest total nitrogen in effluent, corroborating our results. Negative correlation was determined between effluent parameters and certain taxa: effluent conductivity and Opercularia coarctata abundance (R S = −0.62, p < 0.05), total bacteria in effluent and number of taxa (R S = −0.68, p < 0.05), total N in effluent and Vorticella sp.…”
Section: Municipal and Industrial Wastewatersupporting
confidence: 93%
“…In addition, Aspidisca cf. cicada is one of the most frequently reported species in WWTP receiving industrial inputs (Dubber and Gray, 2011;Sobczyk et al, 2020); its occurrence is in line with the characteristics of the studied plant where the high concentration of ammonia and toxic tannery wastewater is treated. Phialina sp., the free-swimming carnivorous ciliate, appeared five times out of six samples; its high occurrence might reflect another characteristic of the studied plant, that is the presence of a well-structured food web (see below).…”
Section: General Overview On Ciliate Community and Its Compositionmentioning
confidence: 56%
“…Among them, Aspidisca cf. cicada, Euplotes spp., and P. calkinsi are known to have strong ecological tolerance, e.g., they can survive in highly polluted water bodies (Madoni et al, 1992;Madoni et al, 1994;Puigagut et al, 2005;Sobczyk et al, 2020) and develop high-density populations. In addition, Aspidisca cf.…”
Section: General Overview On Ciliate Community and Its Compositionmentioning
confidence: 99%